Digital Application of Echolalia Behavioral Assessment for Teachers in Conducting Assessments of Autistic Students in Surakarta - Wulandari, Retno; Gunarhadi, Gunarhadi; Widyastono, Herry (Angstrom Centre of Education, 2022)
This study aims to describe and provide solutions to obstacles to echolalia behavior assessment in autistic students in Surakarta. This research is descriptive qualitative research by digging information from 18 teachers as research subjects. Data collection techniques using interviews and observation. The validity test used in this research is constructed validity which is obtained using validity testing by experts (expert judgment). While the reliability test of the instrument by analyzing the consistency of one's answers to the questions. The results of the study illustrate that there are various obstacles for teachers in providing assessments for autistic students, including (1) limited experts, (2) inadequate infrastructure, and (3) low parental support. As for how to overcome these obstacles, it is done by making a digital application for evaluating echolalia behavior that can make it easier for teachers to provide assessments to autistic students to improve their speaking skills of autistic students. This application contains information about autism, echolalia behavior, its impact, assessment guidelines, and interventions in the form of an android that is practical and easy to use and uses the latest technology.